Autophagy, a novel player in acetaminophen (APAP)-induced hepatotoxicity - Hui Ye; Francisco Javier Cubero (Autophagy Reports, 2022)
Acetaminophen (APAP), a widely used analgesic drug, is safe at therapeutic doses, but can produce significant hepatotoxicity upon overdose. Emerging evidence suggested that endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) are key mechanisms in APAP-mediated hepatotoxicity. While ER stress-UPR and macroautophagy/autophagy appear to be independent cellular processes, we found a cross-linked mechanism in APAP liver injury. The specific ablation in liver parenchyma of XBP1 (X-box binding protein 1), a transcription factor mediating ER stress, mitigates APAP-induced liver injury. Interestingly, this mechanism is linked to enhanced autophagy which seems to be responsible for the modulation of the enzymatic activity of CYP2E1, which is involved in the metabolic conversion of APAP, and ultimately protects liver against APAP toxicity. Altogether, our study highlighted autophagy as a novel player in the pathophysiology of APAP-induced liver injury and opened new therapeutic avenues for its modulation in patients with drug overdose.